Association Between Cadmium Exposure and Kidney Disorder Among Workers in the Battery Industry - Retno Adriyani; Yusrina Nurul Aanisah; Ilyas Ibrahim; Mohd Yusmaidie Aziz; Aulia Choirunnisa' (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Workers in the battery industry are at risk of being exposed to cadmium (Cd), which can cause various health problems, including kidney disorders. This study aims to investigate the association between biomarkers of Cd exposure and effect with kidney disorders among workers in the battery industry. Methods: A systematic review approach was used in this study, employing relevant keywords and inclusion criteria to search electronic databases, such as Google scholar, PubMed, Science Direct, and Research Gate. The selected articles included research articles published between 2010 and 2020, with cross-sectional, cohort, and case-control study designs. To ensure the quality of the articles reviewed, the Critical Appraisal Skill Programme (CASP) was used. Results: The CASP tools facilitated the exploration of trustworthy and relevant articles for the literature review. Previous studies revealed that individuals of various ages, ranging from teenagers to adults aged 12-60, both males and females, are commonly employed in the battery industry. Cadmium was detected in the hair, urine, and blood samples of these workers. Previous studies also identified kidney disorders among these workers by analyzing biomarkers such as creatinine, retinol-binding protein, blood urea nitrogen, and hemoglobin, which were all found to be above the normal range. Furthermore, increased Cd levels in the blood of workers caused glomerular disorder and tubular dysfunction, eventually resulting in kidney function disorders. Conclusion: Cd levels in the bodies of workers in the battery industry serves as a reliable biomarker of Cd exposure, and are closely related to the number of effect biomarkers that can contribute to kidney disorders. This study emphasizes the importance of monitoring Cd exposure levels among workers in the battery industry.